Robotic-assisted left adrenal cystic mass excision in a pregnant patient. Issue 6 (1st June 2022) - Champion, Nicholas Tyler; Monasterio, Diego; Mukherjee, Indraneil; Picon, Antonio
Abstract : A symptomatic adrenal mass diagnosed during pregnancy is a rare clinical scenario. Two primary considerations are the timing of intervention and determining the appropriate surgical approach. Here, we present the case of a young female patient with flank pain, whom on diagnostic imaging, was found to have a large cystic adrenal mass. She was taken for a robotic-assisted resection of her left-sided adrenal mass during the second trimester of pregnancy. Preoperative and postoperative assessment demonstrated a viable intrauterine pregnancy. She tolerated the procedure well and was discharged 5 days later with resolution of her symptoms on follow-up. As one of only three reported cases of robotic adrenal surgery during pregnancy, we demonstrate that a robotic-assisted surgical approach is a viable and durable surgical option under the given clinical circumstances.